2020
DOI: 10.1159/000510688
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Olfactory Inputs within the Central Nervous System of a Cartilaginous and a Bony Fish: An Anatomical Indicator of Olfactory Sensitivity

Abstract: The volume of the olfactory bulbs (OBs) relative to the brain has been used previously as a proxy for olfactory capabilities in many vertebrate taxa, including fishes. Although this gross approach has predictive power, a more accurate assessment of the number of afferent olfactory inputs and the convergence of this information at the level of the telencephalon is critical to our understanding of the role of olfaction in the behaviour of fishes. In this study, we used transmission electron microscopy to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 103 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…Studies have investigated potential reasons for interspecific variation. Researchers have not been able to correlate organ size and complexity to odor sensitivity in teleosts nor elasmobranchs, indicating that rosette size may not be a good proxy for odor detection abilities (Camilieri‐Asch, Yopak, et al, 2020; Hansen & Zielinski, 2005; Meredith & Kajiura, 2010). While a potential relationship between size of teleosts and the number of olfactory lamellae, this has not been found in elasmobranchs and rosette size was shown to be positively correlated with body size (Ferrando et al, 2017; Pashchenko & Kasumyan, 2017; Schluessel et al, 2010; Theiss et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have investigated potential reasons for interspecific variation. Researchers have not been able to correlate organ size and complexity to odor sensitivity in teleosts nor elasmobranchs, indicating that rosette size may not be a good proxy for odor detection abilities (Camilieri‐Asch, Yopak, et al, 2020; Hansen & Zielinski, 2005; Meredith & Kajiura, 2010). While a potential relationship between size of teleosts and the number of olfactory lamellae, this has not been found in elasmobranchs and rosette size was shown to be positively correlated with body size (Ferrando et al, 2017; Pashchenko & Kasumyan, 2017; Schluessel et al, 2010; Theiss et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are five main ORN morphotypes currently described in teleosts: ciliated, microvillous, crypt (Fishelson et al, 2010 ; Kermen et al, 2013 ; Muller, 1984 ), kappe (Ahuja et al, 2014 ), and pear (Calvo‐Ochoa & Byrd‐Jacobs, 2019 ). Although empirical identification of individual subtypes was outside of the scope of this study, as they cannot be confirmed without immunohistochemistry (e.g., Camilieri‐Asch, Yopak, et al, 2020 ), the presence of OKs with apparent morphological differences between fry and adult specimens suggests there may be ontogenetic changes in ORN subtype number and density. However, it is important to approach this with caution, as morphological differences from SEM can be due to fixation artifacts or tissue preparation, rather than true anatomical variation.…”
Section: Discussionmentioning
confidence: 84%
“…The dimensions of the olfactory bulbs were often used to determine the olfactory capacity of a species and would indicate the significance of the olfactory sense in E. lucifer (Camilieri‐Asch, Shaw, et al, 2020 ; Camilieri‐Asch, Yopak, et al, 2020 ; Schluessel et al, 2008 , 2009 ; Theisen et al, 1986 ; Zeiske et al, 1987 ). The sheer size of the nasal capsules does not necessarily allow conclusions on the efficiency of the olfactory system (Gardiner et al, 2012 ; Meredith et al, 2012 ; Meredith & Kajiura, 2010 ), however, Camilieri‐Asch, Yopak, et al ( 2020 ) claim that the dimensions of the olfactory bulbs are correlated with the number of olfactory stimuli through the epithelium. They conclude that the dimensions can be considered a valid proxy for olfactory ability in elasmobranchs.…”
Section: Discussionmentioning
confidence: 99%